Mechanical and electrical properties of Y-TZP/ZrB2 composite - Amiriyan, Mahdi; Kelvin, Chew W.J.; Ramesh, S.; Tolouei, Ranna; Hassan, M.A.; Sopyan, Iis; Meenaloshini, S. (2012)
Over the last three decades, most of the efforts in mechanics of materials science have been focused to develop tougher and stronger ceramics via cost effective processing techniques. In the present work, 3 mol % Yttria-stabilized tetragonal zirconia (3Y-TZP) composites with 25 wt. % of ZrB2 was prepared by pressureless sintering method in argon atmosphere over the temperature range of 1350-1550°C for one hour holding time. The influences of zirconium diboride addition in the zirconia matrix, as well as the sintering temperature, on the densification, phase stability and electrical properties of sintered samples have been studied. The results revealed that electrical resistivity values is very low (high electrical conductivity) when 25 wt. % of ZrB2 is incorporated to pure 3Y-TZP.